Does Socio-Economics Factor Influence Beef Cattle Farmers' Ability to Adapt to Climate Change? - Putri, Salwa Noor; Hartono, Budi; Putritamara, Jaisy Aghniarahim; Satria, Awang Tri; Purwanti, Tina Sri (Jurnal Ilmu-Ilmu Peternakan, 2023)
The livestock industry is still struggling with the effects of climate change. All commodities, including beef cattle, are subject to the negative effects of climate change. One such effect is heat stress, which can result in losses in the form of reduced reproduction and productivity as well as welfare losses. The negative effects of climate change must be reduced through prevention, which includes adaptation. Beef cattle farmers make several different modifications. Socioeconomic considerations are one of the many types of factors that can contribute to this modification. This research was conducted in Probolinggo, Sumenep, and Tuban districts because these three areas have the largest beef cattle population in East Java. We interviewed 206 farmers using a questionnaire. The acquired data were examined using quantitative descriptive analysis and STATA 17 software with a multivariate probit model. This study discovered that beef cattle farmers used four adaptation strategies to deal with climate change, such as changing forage types to provide more nutrition; having routine immunization; working with veterinarians to improve biosecurity, vaccination, and animal health; and promoting artificial insemination using high-quality semen. Furthermore, socioeconomic determinants that have a major impact include age, access to credit, farming experience, level of education, access to non-farming income, and access to climate change knowledge. However, gender, family size, and livestock size had no effect on adaptation